Turbulent boundary-layer control with DBD plasma actuators using spanwise travelling-wave technique - Whalley, Richard David (2011)
Turbulent boundary-layer control has been investigated experimentally using a low-speed wind tunnel at the University of Nottingham, with an overall aim of achieving skin-friction drag reduction. The important part of this investigation is to understand the mechanism of drag reduction and the associated changes in the structure of the turbulent boundary layer. It was demonstrated with Direct Numerical Simulations (DNSs) nearly a decade ago that by applying a spanwise travelling wave in the near-wall region of a turbulent wall flow can lead to a skin-friction drag reduction on the order of 30%. To date, spanwise travelling waves are predominantly created by a Lorentz force, limiting the study of this technique to water flows and numerical investigations. As an aeronautical application of this innovative flow control technique, an investigation into the use of Dielectric-Barrier-Discharge (DBD) plasma actuators to generate spanwise travelling waves in air has been conducted. DBD plasma actuators have received enormous interest over the past ten years within the flow control community due to their unique properties. DBD plasma actuators are completely electrical and ionize the nearby air to couple momentum to the surrounding flow. Hence, DBD plasma actuators require no moving parts, which makes their design simple and without the need for complicated ducting, holes or cavities. They are fast acting, of low power, low in weight, cheap to manufacture and can be fitted to existing airframes. As the body force that the DBD plasma actuator creates is at the wall, DBD plasma actuators are an ideal candidate for wall-based flow control techniques such as the spanwise travelling wave-technique. In this study, DBD plasma actuators have been found to have the ability to greatly modify the near-wall region of the turbulent boundary layer with a potential to reduce skin-friction drag. The near-wall structures modified by the spanwise travelling waves were studied using the PIV technique, while the associated turbulence statistics were carefully documented using hot-wire anemometry. On initiation of DBD plasma in the turbulent boundary layer, streamwise vortices were generated. Spreading of low-speed fluid by the streamwise vortices that were travelling in the spanwise direction was observed, which seems to have greatly attenuated the turbulence production process. This is very much in line with the finding of DNS studies, where wide low-speed ribbons replaced the low-speed streaks.